Surface residual stress distribution for face gear under grinding with a long-radius disk wheel. (August 2019) - Wang, Yanzhong; Chu, Xiaomeng; Huang, Yizhan; Su, Guoying; Liu, Douwei
Highlights: Face gear equation under grinding with long radius disk wheel is established. The mathematical models of grinding force and grinding heat are established. The residual stress analysis model of face gear grinding is established. The residual stress analysis model of face gear is verified by experimental data. Abstract: Face gear transmission has been widely used because of its unique technical advantages. The residual stress of a tooth surface after grinding is the key factor affecting the surface quality of gear teeth. To improve the performance of tooth surfaces and better guide the grinding test, it is necessary to develop a method to analyse the residual stress of face gear after grinding with a long-radius disk wheel. First, a mathematical model of the grinding face gear with a long-radius disk wheel is established. Then, the basic parameters affecting face gear grinding are studied, and mathematical calculation models, including the grinding force and grinding heat, are established. On this basis, the three processes of elastic loading, plastic deformation and stress release are studied, and a mathematical model of the residual stress of face gear grinding is established. Finally, face gear grinding tests are carried out; the residual stress is determined, and the model is verified by experimental data. Through the study of the surface residual stress distribution of face gear under grinding with a long-radius disk wheel, the grinding process can be further guided to improve the grinding quality and can be extended to the analysis of residual stress distribution after grinding of other complex surface parts.